Combat and military-professional stress: the influence of emotions and emotional states on the choice of coping strategies - Khraban Tatiana Evgenievna; Silko Oleksiy Viktorovich (Insight: the psychological dimensions of society, 2022)
The purpose of this empirical research is 1) to study suchcharacteristics of the military cadets’ emotional intelligenceas the ability to identify and manage their emotions;2) to analyze the correlation between preferencefor coping strategies used by military cadets dealing withcombat and military-professional stress and emotionsexperienced by these cadets. Materials and methods.The study was conducted in April 2022. The respondents were third-year cadets of the Military Institute of Telecommunicationand Information Technologies studyingfor a Bachelor of Military Science in Military Management.The first stage of research was the activation of cadets’experiences owing to catatymically imaginative technique(representations of images) – they were askedto draw symbolic images of their ordeals. In the secondstage we used self-report technique. The cadets wereasked to describe their emotions towards the eventsthey had experienced and the actions they took to createa balance between themselves and the external situation.The results were analyzed through descriptive statisticsand Pearson’s correlation coefficient analysis. Results.22.0% of the cadets failed to understand and identifytheir emotions – they were unable to name their emotionsregarding the events they experienced and to drawsymbolic images of their experiences. 78.0% of the cadetswere able to identify their emotions. The cadets experiencedcomplex emotions, but in which it was possible todistinguish such basic components: anxiety, anger, apathyand hope. A total of 32 emotions were listed. This fact canindicate cadets’ clear understanding of their emotionalstate through the pressure of some emotions. The choiceof coping strategies was made on the basis of optimistic/pessimistic interpretation of a stressful situation. Conclusions.The impact of the following factors needs tobe taken into account for studying servicemen’ ability toexpress and manage their emotions: 1) an integral partand key normative component of military subculture isemotion suppression and emotional avoidance, whichmay be adaptive in the short term when other strategiesare not available; 2) there is a danger of chronic,overwhelming combat and military-professional stress,which is associated with the specifics of military activity;3) there is the risk of occurrence of a stress-related problemswith feeling emotions (alexithymia), in which thereare a deterioration of symbolizing capability, a growingtendency towards concrete, logical thinking on the backgroundof deficiency of emotions; the risk of developmentof a psychological condition of an emotional storm, whenemotions take over so that it is difficult to handle them,or an emotional condition of nervous exhaustion, depressionand indifference to what is happening. Therefore,the study of the emotional intelligence of military personnelrequires the development of special tools. Thereis a significant correlation between preference for copingstrategies used by military cadets dealing with combatand military-professional stress and emotions experiencedby these cadets.